Magnetic structure, dipole reversals, and 1/f noise in resistive MHD spherical dynamos - Fontana, Mauro (2018)
A parametric study of the magnetic dipole behavior in resistive incompressible magnetohydrodynamics inside a rotating sphere is performed, using direct numerical simulations and considering Reynolds and Ekman numbers as controlling parameters. The tendency is to obtain geodynamolike magnetic dipole reversal regimes for sufficiently small Ekman and large Reynolds numbers. The typical dipole latitude obtained in the reversal regime is around 40-(with respect to the rotation axis of the sphere). A statistical analysis of waiting times between dipole reversals is also performed, obtaining a non-Poissonian distribution of waiting times, indicating long-term memory effects. We also report the presence of a 1/f frequency power spectrum in the magnetic dipole time series, which also shows a tendency to grow toward lower frequencies as the Ekman number is decreased.